Ayurveda Management of Alcoholic Hepatitis - Acharya, Shripathi; Acharya, Rajeshwari S (International Research Journal of Ayurveda & Yoga, 2024)
In Indian population Chronic alcoholism and Alcoholic Hepatitis are commonly encountered. Excessive and chronic intake of alcohol causes liver damage and subsequent Hepatitis. In Ayurveda it is called Madhyajanya Yakrit Vikara resembles kamala which is a pittajanya vyadhi. Madya effects as a poison if a person drinks it in appropriate manner The metabolite of alcohol i.e acetaldehyde causes damage to hepatocytes and causes inflammation of the liver leading to increased formation of liver enzymes and serum bilirubin in the circulating blood. It causes yellowish discolouration of conjunctiva, urine and skin. There will be symptoms like loss of appetite, body ache, mild fever, weakness in the lower limbs and often itching. Ayurveda management in this include stoppage of alcohol followed by Vyadhi pratyanika chikitsa, adequate rest, Pathy-apathya prayoga, walking daily, use of hepato-protective drugs, Satvavajaya chikitsa , counseling and Pranayama therapy. Alcoholic hepatitis cases can be successfully treated by Ayurveda medicines. In this paper Ayurveda treatment of Alcoholic hepatitis is discussed in detail.